Stable Multi-Wavelength Thulium-Doped All-Fiber Laser Incorporating a Multi-Cavity Fabry–Perot Filter - A. Camarillo-Aviles; D. Jauregui-Vazquez; J. M. Estudillo-Ayala; E. Hernandez-Escobar; J. M. Sierra-Hernandez; O. Pottiez; M. Duran-Sanchez; B. Ibarra-Escamilla; M. Bello-Jimenez (IEEE Photonics Journal)
The present manuscript experimentally demonstrates multi-wavelength generation from a thulium-doped all-fiber laser by implementing a multi-cavity Fabry-Perot filter. The filter, with a composition that relies of several silica-air and air-silica interfaces, provide a spectral reflection response that allows the laser to be operated in single-, dual- or triple-wavelength emissions by simple and clear adjustment of the polarization state. In this way, the fiber laser is capable to operate over a broad range of wavelengths extending from 1844 to 1928 nm. In addition, dual-wavelength operations are also feasible in the 1844 and 1928 nm regions, exhibiting a mode spacing of 4.41 nm and 1.62 nm, respectively. Beside this, the laser is able to switch to a sextuple-wavelength operation regime in the 1885 nm region, maintaining a minimum wavelength spacing of 1.53 nm. The laser demonstrates high wavelength stability, with variations below 60 pm at all analyzed wavelengths, and a minimum peak power fluctuation of ±2.77 dB.